A Th2-Type Response Is Associated With Exuberant Lesions in Pregnant Women Infected With Leishmania braziliensis. (27th August 2018) - Dutra, Walderez O; Barbosa, Daniela Faria; de Souza, Paulo Eduardo Alencar; Morgan, Daniel; Poetker, Shelene; Guimarães, Luiz Henrique; Bacelar, Olívia; Gollob, Kenneth J; Carvalho, Edgar M
Abstract: Background: Cutaneous leishmaniasis (CL) is characterized by an exaggerated inflammatory response. During pregnancy there is a decreased inflammatory response, and we have shown that pregnant women with CL develop exuberant lesions. Methods: Cytokine production by peripheral blood mononuclear cells and the frequency of cells expressing cytokines in lesions from pregnant and nonpregnant women with CL were evaluated. Results: We observed that CL lesions from pregnant women displayed a more intense cellular infiltrate, associated with an increase in neutrophils and CD4 + cells. While no difference was observed regarding the number of interferon-gamma (IFN-γ) + cells in lesions from pregnant compared to nonpregnant women with CL, interleukin-10 (IL-10) and IL-4 expression were approximately 3-times higher in lesions in pregnant women. Main sources of IL-4 and IL-10 were CD4 + and CD68 + cells, respectively. Expression of IL-4, but not IFN-γ or IL-10, was positively correlated with the intensity of inflammatory infiltrate in lesions from pregnant women. Conclusions: These results provide evidence of an IL-4–mediated pathology in Leishmania braziliensis -infected pregnant women. These differences in lesion pathogenesis in pregnant and nonpregnant women may open possibilities for new therapies for CL treatment during pregnancy, which are currently lacking. Abstract : This study shows an association between the severe lesions observed in pregnant women infected with Leishmania braziliensis and the occurrence of a strong Th2-type response. This work provides evidence of an IL-4–mediated pathology in human L. braziliensis infection.